THE IMPLEMENTATION OF COMPUTER ASSISTED LANGUAGE LEARNING IN TEACHING SPEAKING NI ELF CLASSROOM - Ihsanuddin, - (2009)
This thesis reports on the issues of the implementation of CALL and its benefits and hindrances in Teaching speaking in EFL classroom. Analysis of the research literature in this study revealed that models of CALL could be classified based on the setting where CALL was implemented: one -computer classroom; multiple-computer classroom; and computer laboratory. This thesis employed a qualitative research design; a case study in particular. The data were obtained from several sources, including classroom observations, questionnaire- given after the classroom observation and analyzed by using descriptive statistics, interviews immediately after the classroom observation, and document analysis relating to the lesson plan done before classroom observation. This study revealed that models of CALL used by the English teachers could be classified into one-computer classroom; and multiple-computer classroom. The results of the study were consistent and support previous work performed by Smaldino (2005 and Dudeney and Hockely (2007). This study also showed that the implementation of CALL is beneficial, in that: CALL provides ample exposures (opportunities to hear and see the models of target language); enhances the students' confidence to use the target language; creates the class more active with various learning activities; develops student-centered learning; and provides authentic material for learning. However, this study found that there have been some issues that still need to be solved in using CALL in the classroom. These are, among others, to do with reliance on software program, the need of updating periodically, and much electricity consumption. It is recommended that a study for the same topic should be conducted involving more participants, in other contexts, in different school and level of education.